"That is just what they want you to believe": A modest defence of Marxist paranoia. (27th February 2018) - Olsson Yaouzis, Nicolas
Abstract: This essay defends a rational reconstruction of a genealogical debunking argument that begins with the premise "that's just what the economic elite want you to believe" and ends in the conclusion "you should lower your confidence in your belief." The argument is genealogical because it includes a causal explanation of your beliefs; it is debunking because it claims that the contingencies uncovered by the genealogy undermine your beliefs. The essay begins by defending a plausible causal explanation of your belief in terms of the wants of the elite. Then a number of recent objections to genealogical debunking arguments are considered. It is argued that the genealogy offered in the first part constitutes evidence that a testimony‐based belief is not safe and therefore does not constitute knowledge if the economic elite wants you to believe it.